Clinical Feedback About Empirically Supported Treatments for Obsessive‐Compulsive Disorder. Issue 1 (January 2016) - Jacobson, Nicholas C.; Newman, Michelle G.; Goldfried, Marvin R.
Abstract: Previous evidence for the treatment of obsessive‐compulsive disorder (OCD) has been derived principally from randomized controlled trials. As such, evidence about the treatment of OCD has unilaterally flowed from researchers to clinicians. Despite often having decades of experience treating OCD, clinicians' feedback on their clinical observations in using these treatments has not been solicited. The current study contacted clinicians for their clinical observations on empirically supported treatments for OCD to identify commonly used cognitive-behavioral techniques and their limitations in their practices. One hundred eighty-one psychotherapists completed an online survey. The average participant practiced psychotherapy for 15 years, worked in private practice, held a doctorate, and treated an average of 25 clients with OCD in their lifetime. In regard to the most common techniques, behavioral strategies involving exposure to a feared outcome and prevention of a compulsive ritual were the most frequent group of interventions, followed by techniques that attempted to identify and challenge irrational thoughts. However, the majority of participants also reported incorporating mindfulness or acceptance-based methods. Based on therapists' reports, the most common barriers to the efficacy of cognitive-behavioral interventions included limited premorbid functioning, chaotic lifestyles, controlling and critical families, OCD symptom severity, OCD symptom chronicity, and comorbidities. This study provides insight into common practices and limitations in clinical practice to inform future clinically relevant treatment research. Highlights: Reports on clinicians' feedback about empirically supported treatments for OCD Clinicians report ERP is commonly used in their practice to treat OCD Respondents primarily held doctorates, worked in private practice, and practiced CBT Respondents reported using an assortment of methods in the assessment and treatment of OCD Premorbid functioning, chaotic lifestyles, critical families impede treatment efficacy